Antimicrobial Efficacy of Cardamom and Star Anise Powders on E. coli O157:H7 and other Microbial Quality Indicators in Minced Beef under Refrigeration Storage (5±1oC) - Kumar, A. Vinoth; Pal, U. K.; Mandal, P. K.; Kasthuri , S.; Antony, P. X. (Journal of Meat Science, 2018)
Now-a-days consumers prefer natural foods without chemical preservatives. In this context, the present study was undertaken to evaluate antimicrobial efficacy of cardamom and star anise powders against E. coli O157:H7 and other common microbial indicators in minced beef during refrigeration storage (5±1oC). Reduction in E. coli O157:H7 population in 2 percent star anise powder treated samples was significantly (P<0.05) higher than samples treated with 2 percent cardamom powder and control samples. The standard plate count, coliform counts, psychrophilic and yeast and mold counts (log cfu/g) of treatment groups were significantly (P<0.001) lower than control throughout the storage period. Samples treated with 2 percent star anise powder showed significant (P<0.001) decrease in all microbial counts than 2 percent cardamom powder and control group. The addition of the 2 percent cardamom and 2 percent star anise powders into minced beef exhibited antimicrobial activity and successfully extended its shelf life to 5 and 6 days, respectively compared to 3 days in control samples at 5±1◦C.